Fabrication of knock- down sheetmetal stool (Dadesen) - Amui, Sinards Seth Tetteh (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirements for the award of Master of Arts degree, 2001